Single-cell transcriptional responses of T cells during microsporidia infection - Yunlin Tang; Lu Cao; Jiangyan Jin; Tangxin Li; Yebo Chen; Yishan Lu; Tian Li; Louis M. Weiss; Guoqing Pan; Jialing Bao; Zeyang Zhou (Communications Biology)
Abstract T cells have been reported to play critical roles in preventing of microsporidia dissemination. However, there roles and functions of each subset remain unclear. Here in the study, we performed a thorough analysis of murine splenic T-cell response analysis via single-cell RNA sequencing during microsporidia E. cuniculi infection. We demonstrated that Type I T helper (Th1) cells, T follicular helper (Tfh) cells, effector CD8 + T cells and proliferating CD8 + T cells were activated and expanded after infection. Activated Th1 cells and Tfh cells presented significantly upregulated gene expression of Ifng and Il21, respectively. A subcluster of Th1 cells with high Csf1 expression was detected after infection. Subsets of activated CD8 + T cells were markedly enriched with high expression of cytotoxic-function related genes such as Gzma and Gzmb, whereas some active CD8 T cells were enriched with proliferation-function related genes Mki67 and Stmn1. Other subsets of T cells including NK T cells, Myb+ T cells, γδ T cells and Cxcr6+ T cells, were also analyzed in this study yet no expansion was observed. In summary, our findings provide in-depth and comprehensive insights into T-cell responses during microsporidia infection, which will be valuable for further investigations.